Risks of adverse pregnancy and birth outcomes in women treated or not treated with mood stabilisers for bipolar disorder: population based cohort study. (8th November 2012) - Bodén, Robert; Lundgren, Maria; Brandt, Lena; Reutfors, Johan; Andersen, Morten; Kieler, Helle
Abstract : Objective To investigate the risks of adverse pregnancy and birth outcomes for treated and untreated bipolar disorder during pregnancy. Design Population based cohort study using data from national health registers. Setting Sweden. Participants 332 137 women with a last menstrual period anytime after 1 July 2005 and giving birth anytime before the end of 31 December 2009. Women with a record of at least two bipolar diagnoses were identified and grouped as treated (n=320)—those who had filled a prescription for mood stabilisers (lithium, antipsychotics, or anticonvulsants) during pregnancy—or untreated (n=554). Both groups were compared with all other women giving birth (n=331 263). Main outcome measures Preterm birth, mode of labour initiation, gestational diabetes, infants born small or large for gestational age, neonatal morbidity, and congenital malformations. Results Of the untreated women, 30.9% (n=171) were induced or had a planned caesarean delivery compared with 20.7% (n=68 533) without bipolar disorder (odds ratio 1.57, 95% confidence interval 1.30 to 1.90). The corresponding values for the treated women were 37.5% (n=120) (2.12, 1.68 to 2.67). The risks of preterm birth in both treated and untreated women were increased by 50%. Of the untreated women, 3.9% (n=542) had a microcephalic infant compared with 2.3% (324 844) of the women without bipolar disorder (1.68, 1.07 to 2.62). The corresponding values for the treated women were 3.3% (n=311) (1.26, 0.67 to 2.37). Similar trends were observed for risks of infants being small for gestational age infants for weight and length. Among infants of untreated women, 4.3% (n=24) had neonatal hypoglycaemia compared with 2.5% (n=8302) among infants of women without bipolar disorder (1.51, 1.04 to 2.43), and 3.4% (n=11) of the treated women (1.18, 0.64 to 2.16). The analyses of variation in outcomes did not support any significant differences between treated and untreated women. Conclusions Bipolar disorder in women during pregnancy, whether treated or not, was associated with increased risks of adverse pregnancy outcomes.